Pengaruh Entreprenuerial Leadership Terhadap Organizational Performance : Mediasi Learning Organization Dan Organizational Commitment Pada Hotel Bintang Empat - Soleh, Mohammad (UMSurabaya Publishing, 2023)
This study aims to analyze the influence of entrepreneurial leadership on organizational performance at four-star hotels in East Java, with mediating role of learning organization and organizational commitment. The research sample consisted of 71 respondents from the leadership or management of a four-star hotel in East Java, and the research methodology used an explanatory research approach. PLS-SEM is the analytical method used. The results show entrepreneurial leadership has a positive and significant effect on learning organizations and organizational commitment, learning organization and organizational commitment have a positive and significant effect on organizational performance, learning organization and organizational commitment both significantly mediate the influence of entrepreneurial leadership on organizational performance. There is one rejected hypothesis, entrepreneurial leadership has no significant effect on organizational performance.Studi ini bertujuan menganalisis pengaruh kepemimpinan kewirausahaan terhadap kinerja hotel bintang empat di Jawa Timur, dengan peran mediasi dari learning organization dan komitmen organisasi. Rancangan penelitian menggunakan pendekatan explanatory research, dengan sampel penelitian adalah pimpinan atau manajemen hotel bintang empat di Jawa Timur dengan jumlah sampel sebanyak 71 responden. Teknik analisis menggunakan Partial Least Square-SEM (PLS-SEM). Temuan penelitian menunjukkan organisasi pembelajaran dan komitmen organisasi dipengaruhi secara signifikan oleh kepemimpinan kewirausahaan, keduanya juga berpengaruh signifikan terhadap kinerja organisasi, serta berperan sebagai mediator yang signifikan dari kepemimpinan kewirausahaan terhadap kinerja organisasi. Selanjutnya ada satu hipotesis yang ditolak yaitu kepemimpinan kewirausahaan tidak terbukti berpengaruh terhadap kinerja organisasi.entrepreneurial leadership, learning organization, organizational commitment, organizational performance